2005
DOI: 10.1002/pmic.200401069
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of breast cancer: Enhanced expression of cytokeratin19 in human epidermal growth factor receptor type 2 positive breast tumors

Abstract: The human epidermal growth factor receptor, type 2 (HER-2/neu or c-erbB-2) is a 185 kDa transmembrane protein that is phosphorylated upon ligand binding and dimerization with members of the HER/c-erbB family and regulates cell growth and differentiation. Its overexpression is strongly associated with advanced disease, metastasis and poor clinical outcome. To better understand the mechanisms underlying the poor prognosis of breast tumors with HER-2/neu-positive status, parallel proteomic analyses were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 53 publications
(34 reference statements)
2
47
0
1
Order By: Relevance
“…A previous study showed that KRT19 was increased in HER2-positive tumors. 26 They concluded that KRT19 might be responsible for driving the phenotypes of HER2-positive tumors; however, they did not provide any mechanistic relationship between HER2 and KRT19.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that KRT19 was increased in HER2-positive tumors. 26 They concluded that KRT19 might be responsible for driving the phenotypes of HER2-positive tumors; however, they did not provide any mechanistic relationship between HER2 and KRT19.…”
Section: Discussionmentioning
confidence: 99%
“…The protein spots were manually excised from the gel and digested with trypsin, as described previously (19). After being dehydrated with acetonitrile and dried in a SpeedVac centrifuge, the gels were re-swelled with 20-40 μl digestion solution containing 20 mM ammonium bicarbonate and 20 ng/μl of sequencing grade trypsin (Promega, Madison, WI, USA) and treated at 37˚C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…After equilibration for 2x15 min in equilibration buffer, IPG strips were applied for SDS-PAGE (12%) using a PROTEAN ® II xi Cell system (Bio-Rad, Hercules, CA, USA). The separated proteins were visualized by silver staining (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this disease, malignant cells often disseminate to regional lymph nodes and establish distant metastases, preferentially in the bone, lung, and liver, resulting in poor outcome and high mortality (2,3).…”
mentioning
confidence: 99%